REGIONAL ASPECTS OF FAMILY HOLDINGS STRUCTURE IN THE REPUBLIC OF SERBIA - Božić, Dragica; Munćan, Petar (Economics of Agriculture, 2015)
Considering the importance of the size of the land property in regard to the development of agriculture and its effectiveness, the ownership structure, its interdependence with the available labour force (the number of persons and annual work units) and economic size of family holdings, are analysed in the present study. Given that the territory of the Republic of Serbia is very heterogeneous in terms of the achieved level of economic development of certain regions, as well as available resources for the development of agriculture, the structural characteristics are analysed in following four statistical regions: Vojvodina, Belgrade, Šumadija and Western Serbia, Eastern and Southern Serbia. Key indicators of family holding structure in Serbia are compared with the average for the EU-27. The aim of the present paper is to review the basic aspects of structural characteristics of family holdings, based primarily on the size of holdings/holdings, available labour force, economic size, as well as their regional diversity in 2012, according to Agricultural Census.